2017
DOI: 10.1161/cir.0000000000000471
|View full text |Cite|
|
Sign up to set email alerts
|

2016 AHA/ACC Guideline on the Management of Patients With Lower Extremity Peripheral Artery Disease: A Report of the American College of Cardiology/American Heart Association Task Force on Clinical Practice Guidelines

Abstract: PreambleSince 1980, the American College of Cardiology (ACC) and American Heart Association (AHA) have translated scientific evidence into clinical practice guidelines with recommendations to improve cardiovascular health. These guidelines, based on systematic methods to evaluate and classify evidence, provide a cornerstone of quality cardiovascular care.In response to reports from the Institute of Medicine1,2 and a mandate to evaluate new knowledge and maintain relevance at the point of care, the ACC/AHA Task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
1,206
2
56

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 788 publications
(1,282 citation statements)
references
References 393 publications
18
1,206
2
56
Order By: Relevance
“…This finding emphasises the importance of optimising treatment in the general peripheral artery disease population. 4,25,26 Consistent benefits in the reduction of major adverse cardiovascular events and major adverse limb events occurred with combination of rivaroxaban 2·5 mg plus aspirin compared with aspirin alone but did not occur to the same extent with the rivaroxaban 5 mg twice a day regimen. These results are also consistent with the results of the overall trial, which have been reported separately.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This finding emphasises the importance of optimising treatment in the general peripheral artery disease population. 4,25,26 Consistent benefits in the reduction of major adverse cardiovascular events and major adverse limb events occurred with combination of rivaroxaban 2·5 mg plus aspirin compared with aspirin alone but did not occur to the same extent with the rivaroxaban 5 mg twice a day regimen. These results are also consistent with the results of the overall trial, which have been reported separately.…”
Section: Discussionmentioning
confidence: 95%
“…4 In addition to smoking cessation and exercise, statins, angiotensin converting enzyme (ACE) inhibitors, and antiplatelet agents (aspirin or a P2Y12 inhibitor) are used to reduce vascular complications. [4][5][6] Anticoagulant therapies have not been shown to be superior to antiplatelet therapy in peripheral artery disease and have unacceptably high rates of major bleeding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Medical therapy for cardiovascular risk prevention in PAD has been reviewed elsewhere and updated in the recent AHA/ACC lower extremity guidelines. 20, 21 As outlined in the Table, several therapies have proven efficacy to reduce cardiovascular risk in PAD and are recommended as guideline-directed therapy.…”
Section: Reduced Limb Perfusion Caused By Arterial Obstructive Lesionsmentioning
confidence: 99%
“…In the present case, due to renal failure, we were reluctant to perform contrast agent injection as a primary tool of proximal ischemia [7]. The initial Ex-tcpO 2 helped confirm the vascular origin of the pain and argued for the injected imaging with revascularization of arterial lesions.…”
Section: Discussionmentioning
confidence: 80%